Empirical single frequency network threshold for DVB-T2 based on laboratory experiments - Ruckveratham, Bundit; Promwong, Sathaporn (My University, 2019)
DVB-T2 broadcasting with a single frequency network (SFN) allows an efficient management of frequency utilization and extends the coverage area, which will enable more people to view a broadcast. The SFN mode also increases the concentration of the signal in overlap areas. However, some difference of overlap areas in actual use of SFN networks may have some degradation of the received signal due to the effect of the SFN. In this research, we analyze SFN broadcasting in SISO mode. This paper represents the effects of delays on the SFN signal over different delay times within the guard interval (GI) by analyzing the minimum reception threshold. The analysis of received signal power, MER, bBER, LBER, and noise margin are studied using an actual digital television transmitter for the experiment. The results show that the minimum thresholds for a delay time at 0 microseconds will require higher receive signal power than other delay times within the GI. The results of this experiment are useful in designing the SFN network and make it possible to determine the appropriate C/N threshold for the design of the digital terrestrial television network.
Keywords: DVB-T2; Reception threshold; Single frequency network